Application of SPH-FE method for fluid-structure interaction using immersed boundary method. Issue 8 (30th October 2018) - Kalateh, Farhoud; Koosheh, Ali
Abstract : Purpose: This paper aims to propose a new smoothed particle hydrodynamics (SPH)-finite element (FE) algorithm to study fluid–structure interaction (FSI) problems. Design/methodology/approach: The fluid domain is discretized based on the theory of SPH), and solid part is solved through FE method, similar to other SPH-FE methods in the previous studies. Instead of master-slave technique, the interpolating (kernel) functions of immersed boundary method are implemented to couple fluid and solid domains. The procedure of modeling completely follows the classic IB framework where forces and velocities are transferred between interacting parts. Three benchmark FSI problems are simulated and the results are compared with those of similar numerical and experimental works. Findings: The proposed SPH-FE algorithm with promising and acceptable results can be utilized as a reliable method to simulate FSI problems. Originality/value: Contrary to most SPH-FE algorithms, the calculation of contact force is not required at interacting boundaries and no iterative process is proposed to calculate forces, velocities and positions at new time step.